2002
DOI: 10.3758/bf03194554
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory forms as a source of information about events

Abstract: The ability to use trajectory forms as visual information about events was tested. A trajectory form is defined as the variation in velocity along a path of motion. In Experiment 1, we tested the ability to detect trajectory form differences between simulations of a freely swinging pendulum and a handmoved pendulum. The trajectory form of the freely swinging pendulum was symmetric around the midpoint, whereas the hand moved was not. In Experiment 2, we isolated trajectory form information by varying the amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Of late, the (topological) structure in phase flows has been used as a conceptual tool for the categorization of (discrete and rhythmic) movements (Huys, Studenka, Rheaume, Zelaznik, & Jirsa, 2008;Jirsa & Kelso, 2005). Phase flow patterns, however, may also underlie the perceptual recognition of distinct motor processes (Perdikis & Jirsa, 2010; see also Muchisky & Bingham, 2002). For the purposes of visual identification of human movement, visual recognition of biological motion may proceed through the extraction of these (macroscopic) dynamical structures (Haken, 1996(Haken, , 2000(Haken, , 2004.…”
mentioning
confidence: 99%
“…Of late, the (topological) structure in phase flows has been used as a conceptual tool for the categorization of (discrete and rhythmic) movements (Huys, Studenka, Rheaume, Zelaznik, & Jirsa, 2008;Jirsa & Kelso, 2005). Phase flow patterns, however, may also underlie the perceptual recognition of distinct motor processes (Perdikis & Jirsa, 2010; see also Muchisky & Bingham, 2002). For the purposes of visual identification of human movement, visual recognition of biological motion may proceed through the extraction of these (macroscopic) dynamical structures (Haken, 1996(Haken, , 2000(Haken, , 2004.…”
mentioning
confidence: 99%
“…Spectators in the stands will see the pitch from various oblique angles, depending on where they are sitting. Muchisky and Bingham (2002) showed that adults can use trajectory forms to identify simple oscillating events seen from the side, but they did not investigate other perspectives. We now will investigate this issue of perceptual constancy in event identification.…”
mentioning
confidence: 99%
“…2 In addition, space is the natural frame of reference in which the trajectory of an event is seen to evolve. Muchisky and Bingham (2002) investigated the sensitivity of adults to the speed component of trajectory forms by systematically manipulating the shape of the speed profile of an oscillator in one of four ways while holding the path and duration constant. The computergenerated event consisted of a circle oscillating back and forth along a straight horizontal path on the computer screen.…”
mentioning
confidence: 99%
“…Muchisky and Bingham [41] investigated the ability of adults to use trajectory forms as visual information about events. They tested whether observers were able to discriminate a freely swinging pendulum and a hand-moved pendulum by detecting trajectory form differences between two events.…”
Section: Direct Perception Theorymentioning
confidence: 99%
“…Direct perceptionists claim that biological motion perception is not special because such point-light demonstrations for the other object events (e.g., bouncing balls, free falling, splashing water) are equally effective [39,40,41]. Bingham et al [40] used patch-light displays for 9 events selected to represent rigid-body dynamics (free fall, pendulum, rolling ball, and struck ball), biodynamics (hand-moved spring and hand-moved pendulum), hydrodynamics (stirred water and splash), and aerodynamics (falling leaves).…”
Section: Direct Perception Theorymentioning
confidence: 99%